KEBANGKITAN MUSLIM TRADISIONAL DI SURAKARTA - Ismail Yahya (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2016)
Islamic resurgence has taken place in the Muslim worlds, including in Indonesia. Representations of this resurgence are depicted by â€œthe outerâ€ dimensions of Islam, and almost represented by the â€œBermazhab Islamâ€ groups, both modernist and revivalist voices by neglecting â€œthe innerâ€ dimensions of Islam and the traditionalist voice (the â€œIslam Bermazhabâ€ groups). This research aims to describe and explain the resurgence among the traditional Islam through majelis zikir, shalawat, taklim, and hadrah. Some interviews, observations, and literature studies were conducted to collect the data. The results are; first, the picture of Islamic resurgence is not balanced. The inner dimensions of Islam and voice of traditional Islam are the forgotten aspects regarding with Islamic resurgence. Second, there is an on-going resurgence among the traditionalists in the form of â€œsantrinisasiâ€ (becoming more pious) and â€œtradisinasiâ€ (habituating) process of Ahlussunah wal-Jamaah teachings and practices. Third, majelis zikir, shalawat, taklim, and hadrah are means to preach and protect the thoughts and practices of the traditionalists. Fourth, there are internal and external factors in this resurgence process. Fifth, the dynamics of this resurgence consist of the resurgence of identity and literature of traditional Islam.